Judy moody goes to college ebook - McDonald, Megan (Judy Moody, 2010)
A few sessions with a college-age math tutor turn Judy into a jargon-spouting polygon princess. Crucial! Judy Moody is in a mood. Not a good mood. And definitely NOT a math mood. The substitute teacher in Class 3T thinks Judy's math skills need improving. So Judy has to start meeting with a math tutor. Does this mean flash cards? Does this mean baby games? Does this mean school on weekends? But when Judy meets her tutor — a sick-awesome college student with an uber-funky sense of style — and gets a glimpse of college life, Judy's bad math-i-tude turns into a radical glad-i-tude. Pretty soon, Judy's not only acing her math class; she's owning it. Time to say good-bye to Judy Moody, old skool third-grader, and say hello to Miss College! Small-tall upside-down backward non-fat capp with extra whip, anyone?